(untitled) (Journal of Asian Development Studies, 2025)
The purpose of this study was to contemplate the relationship between romantic jealousy, marital satisfaction, and self-esteem in married men and women. A correlational design was implemented on the sample of (n=368) married men and women. The sample was collected through the method of purposive sampling from shopping malls, exhibitions, restaurants, parks, and hospitals. The variables were evaluated using assessment measures such as the Romantic Jealousy Scale (α =.70), Couple Satisfaction Index (α =.97), and Rosenberg Self-esteem Scale (α =.52). The correlational analysis revealed there exists a positive correlation between romantic jealousy and marital satisfaction (.31**). There exists a significant inverse correlation between marital satisfaction and self-esteem (-.10). Furthermore, there is another significant positive correlation between romantic jealousy and self-esteem (.27**). The multi-linear regression analysis model reported that romantic jealousy and self-esteem predicted a 12% variance in marital satisfaction in married men and women. The hierarchical regression analysis model demonstrated that marital satisfaction and self-esteem predicted an 18% variance in romantic jealousy in married men and women.